167 EXAMINING PERCEPTIONS ABOUT MENTORING ACROSS MEDICAL STUDENT LEVELS IN ONE SCHOOL. (1st January 2005) - Chauvin, S.; Yang, T.; Mansour, A.; Cauble, S.; Lohmann-Bigelow, J.
Abstract : Purpose: This presentation summarizes completion of a descriptive (baseline) study of students' perceptions of mentoring and the effectiveness of an innovative faculty-resident-student mentoring program. In 2003, LSUHSCmentors, a student-initiated mentoring program, was implemented to facilitate volunteer faculty mentors and interested students engaging in self-initiated and informal mentoring relationships. Methods: A Web-based questionnaire consisting of six sections was developed, field tested, and refined prior to use for this study. Items included Likert or Likert-type response scales (e.g., 1 = strongly disagree to 5 = strongly agree). In June 2004, IRB approval was obtained and the questionnaire was administered on-line to all medical students (n = 699) at LSUHSC using WebQ (LIONIS, Inc., <http:lionis.net >). Descriptive statistical summaries were calculated. Content analysis methods were applied to responses for open-ended items. Results: Questionnaire administration was scheduled originally for April 2004. Delays related to IRB processes resulted in substantial delay in distributing the questionnaire thus resulting in a lower-than-expected response rate (31.47% overall). However, the respondent group was highly similar to the total student population, based on gender and ethnicity. The total set of responses was generally distributed evenly across the four classes/levels of students. Overall, students reported no or few experiences with mentoring prior to medical school and none since for personal concerns. The most common response revealed that student experiences reflect academic advising/guidance encounters more than fully developed mentoring. Common purposes for seeking faculty support were academic and career advising, assistance with academic difficulties, and discussing professional and ethical dilemmas. Response further revealed that students at all levels are very open to mentoring. They report that LSU faculty are approachable and supportive. However, few have actively pursued mentoring and many reported not being aware of the LSUHSCmentors program or the Web site. Most responses suggest a perception that mentoring and academic advising are the same. Conclusion: Most students perceive mentoring as a positive and important component of ongoing academic and professional development. However, they may not fully appreciate the difference between academic advising/guidance functions and a fully developed mentoring relationship. Additional efforts are needed to raise awareness about the LSUHSCmentors and to increase knowledge/skills for using mentoring effectively.